Resilience in the Face of Adversity: Family Processes and the Immigrant Paradox in Youth Externalizing Problems. (July 2022) - Vitoroulis, Irene; Sim, Amanda; Ma, Steven; Jenkins, Jennifer; Georgiades, Katholiki
Background: Despite increased exposure to social adversity, immigrant youth have fewer externalizing problems compared to non-immigrants. Explanations for this apparent advantage remain unclear. This study examined the extent to which socio-economic characteristics and family processes account for group differences in externalizing problems between immigrant and non-immigrant youth. Methods: Data come from a population-based cross-sectional study of 1, 449 youth and their primary caregiver in Hamilton, Ontario. Computer-assisted structured interviews were administered separately to primary caregivers and youth, which included assessments of externalizing problems and measures of family obligation, parental monitoring, value of education and socio-economic characteristics. Results: First- and second-generation immigrant youth had lower levels of externalizing problems compared to non-immigrants. The magnitude of group differences was larger for parent ( d = 0.37–0.55) versus youth reports of externalizing behaviours ( d = 0.15–0.29). Family socio-economic and process characteristics partially accounted for group differences, which remained significant in the parent-reported model but rendered non-significant in the youth-reported model. Conclusion: Results suggesting the potential protective effects of positive family processes for immigrant youth could be extended to non-immigrant youth to inform the development of parenting and family skills interventions. Promoting familial sources of resilience is a potential avenue for reversing downward trends in mental health seen across successive generations of immigrant youth, while also reducing risk of behavioural difficulties among non-immigrant youth.